Induction of tenascin in healing wounds - Mackie, E J; Halfter, W; Liverani, D (The Journal of cell biology, 1988)
The distribution of the extracellular matrix glycoprotein, tenascin, in normal skin and healing skin wounds in rats, has been investigated by immunohistochemistry. In normal skin, tenascin was sparsely distributed, predominantly in association with basement membranes. In wounds, there was a marked increase in the expression of tenascin at the wound edge in all levels of the skin. There was also particularly strong tenascin staining at the dermal-epidermal junction beneath migrating, proliferating epidermis. Tenascin was present throughout the matrix of the granulation tissue, which filled full-thickness wounds, but was not detectable in the scar after wound contraction was complete. The distribution of tenascin was spatially and temporally different from that of fibronectin, and tenascin appeared before laminin beneath migrating epidermis. Tenascin was not entirely codistributed with myofibroblasts, the contractile wound fibroblasts. In EM studies of wounds, tenascin was localized in the basal lamina at the dermal-epidermal junction, as well as in the extracellular matrix of the adjacent dermal stroma, where it was either distributed homogeneously or bound to the surface of collagen fibers. In cultured skin explants, in which epidermis migrated over the cut edge of the dermis, tenascin, but not fibronectin, appeared in the dermis underlying the migrating epithelium. This demonstrates that migrating, proliferating epidermis induces the production of tenascin. The results presented here suggest that tenascin is important in wound healing and is subject to quite different regulatory mechanisms than is fibronectin.